MIGRATION, URBANIZATION, AND DEMOGRAPHIC SHIFTS - Visola Bakhtiyor kizi, Aktamova (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
This article explores the intricate relationships between migration, urbanization, and demographic shifts in contemporary society. As populations increasingly move from rural areas to urban centers, we witness significant changes in demographics, economic structures, and cultural dynamics. The analysis highlights the driving factors behind migration patterns, including economic opportunities, conflicts, and environmental changes. Additionally, it examines the challenges that urbanization brings, such as housing shortages, infrastructure strain, and social integration issues. By understanding these interconnected phenomena, the article aims to provide insights into how migration and urbanization shape our world and the implications for policymakers and communities.